Lama Temple (American Colortype Company)
From the Orient comes this beautiful example of Chinese architecture, a duplicate of the celebrated Golden Temple of Jehol. Within are images of Buddha and other Lama gods, incense burners, prayer wheels, and other paraphernalia.